Analysis of Transmission Characteristics on an MSK-Based Rotating Magnet-Based Mechanical Antenna - Xie He; Qiang Zhou; Jianya Zhang (International Journal of Antennas and Propagation)
A rotating magnet-based mechanical antenna (RMBMA) is a new promising paradigm which can significantly reduce both the size and the power consumption of the super-low frequency electromagnetic transmitter. To further reveal the effects of the rotational motion on transmission, this paper investigates the performance analysis of MSK (Minimum Shift Keying)-based RMBMA for the first time. Initially, based on the framework of MSK-based RMBMA, both the information loading of RMBMA and the control strategies of the motor are proposed, such that the impacts of the step response induced by the motor on the information loading are characterized. Then, the transmission capacity of the MSK-based RMBMA is derived in the closed form. The results indicate that increasing output torque or decreasing inertia load can enhance the transmission capacity. Finally, numerical simulations using a realistic system model demonstrate the validity of the proposed performance analysis. The simulation results show that when the inertia is less than 0.0128 kg∙m2 and the symbol rate is less than 4 bit/s, the bit error rate is less than 10%, thereby improving the transmission capacity. The proposed comprehensive design principles of RMBMA provide guidance for system design and practical implementation.